y=3 cos pi x

I know that the answer is 2 but can you show the steps on how to get there

1 answer

y = 3 cos (πx)

y = 3 (cos π)(x)

y = 3 (-1)(x)

y = -3x

y = -3(1)

y = -3

y = 2 (since -3 + 5 = 2)
Similar Questions
  1. Choose the best answer:1. The L-1, along with the L-3 and L-4, ( show, shows, showing ) some sign of degeneration. Answer: show
    1. answers icon 4 answers
  2. 1) Solve the following by factoring:a) Answer: Show your work here: b) Answer: Show your work here: 2) If , find a) f(2) Answer:
    1. answers icon 1 answer
    1. answers icon 1 answer
  3. QuestionNote: Enter your answer and show all the steps that you use to solve this problem in the space provided. Simplify
    1. answers icon 1 answer
more similar questions